Juvenile Criminal Responsibility in Iraqi Legislation: A Comparative Study with International Conventions (An Analysis of the Age of Responsibility and the Procedures of Investigation and Trial) - Zada Al-Kurdi, Akram (Journal of Legal Studies and Researches, 2026)
This study aims to examine the criminal responsibility of juveniles under Iraqi legislation, with a focus on the procedural safeguards during investigation and trial, and the extent to which these align with international, Arab, and Islamic standards. The research adopts a comparative analytical methodology and reveals that Iraqi law provides important guarantees, yet suffers from weak implementation. The study recommends raising the age of criminal responsibility, activating legal aid, and expanding alternatives to punishment, in a manner that ensures juvenile justice consistent with the best interests of the child.